The oxidation behavior of uranium treated by ultrasonic surface rolling process. (January 2022) - Chen, Daoming; Hu, Yin; Li, Haibo; Li, Fangfang; Guo, Liang; Pan, Qifa; Ma, Ce; Chen, Dong; Liu, Jingyuan; Liu, Kezhao
Abstract: The oxidation behavior of uranium treated by ultrasonic surface rolling process (USRP) was investigated. Optical microscopy (OM), transmission electron microscopy (TEM), x-ray diffraction (XRD), x-ray photo-electron spectroscopy (XPS), auger electron spectroscopy (AES), scanning electron microscopy (SEM), focused ion beam (FIB) and ultraviolet-visible reflectance spectroscopy were used to characterize the microstructure and oxidation behavior of uranium. The oxidation kinetics of USRP treated uranium with pure O2 at 343–388 K was subdivided into two different regimes: a linear-like stage and a parabolic-like stage. The calculated activation energies of USRP treated uranium were approximately 52.3kJ/mol and 75.1kJ/mol for linear and parabolic stages, respectively. The oxide thickness of untreated uranium generally followed a parabolic growth model and the activation energy was 61.4kJ/mol. After the USRP treatment, the nano-grained layer and the close-packed U(002) texture were formed, which promoted the formation of a passive and stable oxidation film on the surface. Meanwhile, the improved surface integrity and the residual compressive stress were obtained, which slowed down the rupture of the oxide layer. As a result, it was concluded that the enhancement of oxidation resistance after USRP treatment was attributed to the nano-grained microstructure, the U(002) texture, the residual compressive stress and the smooth surface. Highlights: The gradient microstructure of nano-grained layer, deformation twinning layer and coarse-grained matrix was obtained by USRP treatment. The calculated activation energies of USRP treated uranium were approximately 52.3 kJ/mol and 75.1 kJ/mol for linear and parabolic stages. The enhancement of oxidation resistance after USRP treatment was attributed to nano-grained layer, U(002) texture, residual compressive stress and smooth surface.